Electrical discharge machining of titanium alloy using copper tungsten electrode with SiC powder suspension dielectric fluid - 330398 Rival (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2005